History and Ethnic Conflict: Does Precolonial Centralization Matter? - Ray, Subhasish (International Studies Quarterly, 2019)
How does the trajectory of precolonial political institutions affect contemporary ethnic conflict? I argue that ethnic groups that were governed by centralized political institutions in the precolonial period are more likely to be associated with armed conflict in the present, but that colonial state-building strategies mediate this relationship. Ethnic groups that experienced precolonial centralization were likely to be underrecruited to the top ranks of colonial security forces prior to independence. This, in turn, increased the chances that those groups would be excluded from the first postindependence regime and hence become involved in armed conflict against the state in the long run. Conversely, colonial security forces tended to overrecruit ethnic groups that did not experience precolonial centralization. This made those groups more likely to become part of the first postindependence regime and less likely to enter into armed conflict against the state in the long run. I provide robust evidence for this pathway by using a self-collected dataset on ethnic groups in ex-British colonies. The findings underscore how contemporary ethnic conflict is embedded in longer-term historical state-building processes in hitherto unappreciated ways.